The South African tide gauge network and its contribution to maritime safety - Farre, Ruth Elizabeth (Department of Oceanography, 2021)
The use of tidal information and its application to, and value within, the study of climate change, sea-level rise and the tides effects on marine life is well known. However, little work has been done on the more technical aspects of tidal measurements and the use within maritime safety in accordance with international standards. This thesis will address the key technical elements in the design and realisation of the national tide gauge network around the South African coastline and how the data collected can be used to increase maritime safety around the South African coast, as well as the additional benefits the data may have both nationally and internationally. The South African Navy's national tide database, both actual records and predictions, as well as current and historical records, was used in order to establish the requirements for a sustainable tide gauge network. In addition, various case studies and data analysis were carried out, as were personal communications with various naval personnel. Establishing and maintaining a sustainable tide gauge network requires research and testing of various tide gauges. Identification of the correct locations to install the tide gauges is key to its success. Although the current South African Tide gauge network is not complete it does provide adequate coverage and is vitally important in the production of navigational products. The manner in which the raw collected tide data is processed and used for creating predictions meets international requirements and standards. Tidal predictions are a necessity for shallow water maritime operations and shallow water navigation, under keel and masthead clearances. The tide gauge network provides data to various organisations for storm surge and tsunami warnings while contributing to the “blue economy” through projects like Operation Phakisa. This thesis provides a comprehensive overview of South Africa's tide gauge network, investigates and justifies the reasons behind the locations and gives in depth examples of the essential use of tidal information for maritime safety.